MicroRNA-129-5p inhibits 3T3-L1 preadipocyte proliferation by targeting G3BP1. Issue 4 (4th July 2017) - Lv, Shun; Ma, Meilin; Sun, Yunmei; Wang, Xiangming; Qimuge, Naren; Qin, Jin; Pang, Weijun
ABSTRACT: MicroRNAs have been regarded to play a crucial role in the proliferation of different cell types including preadipocytes. In our study, we observed that miR-129-5p was down-regulated during 3T3-L1 preadipocyte proliferation, while the expression of G3BP1 showed a contrary tendency. 5-Ethynyl-2′-deoxyuridine (EdU) incorporation assay and flow cytometry showed that overexpression of miR-129-5p could bring about a reduction in S-phase cells and G2-phase arrest. Additional study indicated that miR-129-5p impaired cell cycle-related genes in 3T3-L1 preadipocytes. Importantly, it showed that miR-129-5p directly targeted the 3′ UTR of G3BP1 and the expression of G3BP1 was inhibited by miR-129-5p mimic. Moreover, miR-129-5p mimic activated the p38 signaling pathway through up-regulating p38 and the phosphorylation level of p38. In a word, results in our study revealed that miR-129-5p suppressed preadipocyte proliferation via targeting G3BP1 and activating the p38 signaling pathway.